SYNTHESIS 7-O-CARBOXYMETHYL-3’,4’-DIMETHOXYISOFLAVONE - Andi Hairil Alimuddin; Sabirin Matsjeh; Chairil Anwar; Mustofa Mustofa (Indonesian Journal of Chemistry, 2012)
Synthesis of 7-O-carboxymethyl-3',4'-dimethoxyisoflavone from 7-hydroxy-3',4'-dimethoxyisoflavone derived from eugenol had been done. 7-hydroxy-3',4'-dimethoxyisoflavone was first converted into 7-O-ethoxycarbonylmethyl-3',4'-dimethoxyisoflavone via substitution of hydroxyl group at 7-O position by ethyl-2 chloro acetate through bimolecular nucleophilic substitution reaction (SN2). Hydrolysis of ester group of 7-O-ethoxycarbonylmethyl-3',4'-dimethoxyisoflavone using KOH produce 7-O-carboxymethyl-3',4'-dimethoxyisoflavone in 93.4% yield as a white solid with melting point of 155-159 °C.